2022
DOI: 10.3389/fmicb.2022.994188
|View full text |Cite
|
Sign up to set email alerts
|

Integration of metagenomic and metabolomic insights into the effects of microcystin-LR on intestinal microbiota of Litopenaeus vannamei

Abstract: Microcystin-LR (MC-LR) is a hazardous substance that threaten the health of aquatic animals. Intestinal microbes and their metabolites can interact with hosts to influence physiological homeostasis. In this study, the shrimp Litopenaeus vannamei were exposed to 1.0 μg/l MC-LR for 72 h, and the toxic effects of MC-LR on the intestinal microbial metagenomic and metabolomic responses of the shrimp were investigated. The results showed that MC-LR stress altered the gene functions of intestinal microbial, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…We confirmed a significant increase in the amounts of BAs in the intestinal contents of the APC min/+ mice exposed to MC-LR. Previous studies have shown that reduced concentrations of taurocholate and taurodeoxycholic acid, coupled with increased taurine levels, suggest that MC-LR could influence bile acid metabolic processes [64]. Subsequently, we also noted that the metabolite changes were significantly related to the changes in gut microbial abundance, with TCA having the most positive correlation with Marvinbryantia and Family_XIII_AD3011_group.…”
Section: Discussionsupporting
confidence: 63%
“…We confirmed a significant increase in the amounts of BAs in the intestinal contents of the APC min/+ mice exposed to MC-LR. Previous studies have shown that reduced concentrations of taurocholate and taurodeoxycholic acid, coupled with increased taurine levels, suggest that MC-LR could influence bile acid metabolic processes [64]. Subsequently, we also noted that the metabolite changes were significantly related to the changes in gut microbial abundance, with TCA having the most positive correlation with Marvinbryantia and Family_XIII_AD3011_group.…”
Section: Discussionsupporting
confidence: 63%
“…In line with these results, a previous study reported that acute exposure to MC-LR lowered the relative expression level of cyp7a1 in the liver of Chinese mitten crab ( Hypophthalmicthys molitrix ) [ 36 ]. Another study on shrimp showed that MC-LR exposure decreased the intestinal levels of taurocholate and taurodeoxycholic acid, affecting the bile acid metabolism of shrimp [ 37 ]. Moreover, consistent with the transcriptomic results, metabolic results showed that BA synthesis raw material (taurine) and primary BA (cholic acid and taurocholic acid) levels in the Nile tilapia liver decreased after exposure to MC-LR.…”
Section: Discussionmentioning
confidence: 99%